Hubungan Akuntabilitas Dan Transparansi Sektor Organisasi Nirlaba Pada Lembaga Pemerintahan - Putut Tri H; Rafiansyah R; Rosy Aulia D; Siti Aisyah L; Tommy Satrio W (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Transparency can be interpreted as free access to information and its availability for all parties involved in decision making. Transparency is intended to empower citizens as if they were millions of auditors in society to exercise their right to respond and follow up on policies that have been taken. On the other hand, the lack of transparency means that everyone works as a superior, public institution to prevent the public from accessing information or providing false information. The cause of the lack of transparency is the lack of relationship between the public and officials and the increasing number of corruption cases. Important outcomes of transparency, improving the quality of decisions taken, improving the quality of decision-making, reducing corruption and abuse of positions for personal or partisan interests and informing the public about regulated decision-making processes.